The Media and Their Advertisers: Exploring Ethical Dilemmas in Product Coverage Decisions - Rinallo, Diego; Basuroy, Suman; Wu, Ruhai; Jeon, Hyo Jin (2013)
Marketers are increasingly relying on promotional practices (variously labeled as stealth marketing, hybrid messages, covert advertising) based on the diffusion of product information by third parties that appear to be independent of advertisers. In this paper, we examine to what extent the media treat their advertisers favorably, providing these advertisers’ products extra visibility in supposedly neutral editorial content. Empirically, we model the determinant of media coverage of Italian fashion products in an extended dataset of consumer magazines in Italy, France, Germany, UK, and the USA. Research findings show that advertising is an important determinant of product placements in editorial content, and this result is consistent across countries and publishers. Our results imply that resource-rich advertisers engaging in compensatory advertising (that is, advertising investments that compensate poor product quality) might bias media coverage in their favor. Consumers will consequently be exposed twice to favorable messages about those products, in both advertisements and media content, resulting in higher purchases and reduced consumer welfare.
Keywords: Editorial integrity; Reciprocity; Stealth marketing; Product publicity; Hybrid messages; Freedom of the press; Advertising ethics